Cognitive Behavioral Therapy pada Rehabilitasi Sosial Perempuan Pengguna Narkoba - Bayu Prayoga; Tamrin Bangsu; Syahrio Marta Hila (Universitas Tribhuwana Tunggadewi, 2025)
Drug abuse in Indonesia has increasingly affected women as a vulnerable group facing layered psychosocial consequences, yet gender-sensitive rehabilitation models remain limited. This study addresses this gap by examining the process and distinctive features of Cognitive Behavioral Therapy (CBT) implemented in a women-specific rehabilitation setting at the Karunia Insani Rumah Female Foundation, Rejang Lebong. Using a descriptive qualitative design with a case study approach, this research involved five informants (two counselors and three female clients). Data were collected through in-depth interviews and observations, and analyzed thematically. The findings reveal that CBT is operationalized through a structured yet adaptive three-stage process: (1) an initial phase emphasizing gender-responsive therapeutic alliance and collaborative problem formulation; (2) a middle phase focusing on cognitive restructuring integrated with clients’ lived experiences and relapse triggers; and (3) a final phase highlighting behavioral reinforcement through reflective evaluation and homework assignments. The novelty of this study lies in demonstrating how CBT is contextually adapted to women’s psychosocial vulnerabilities within a community-based rehabilitation setting. The results indicate that such adaptation enhances clients’ cognitive awareness, emotional regulation, and commitment to recovery. This study contributes to the development of gender-responsive rehabilitation models grounded in CBT practice.Penyalahgunaan narkoba di Indonesia semakin menjangkau perempuan sebagai kelompok rentan dengan kompleksitas masalah psikososial, sementara model rehabilitasi yang responsif gender masih terbatas. Penelitian ini bertujuan mengisi kesenjangan tersebut dengan mengkaji proses dan kekhasan penerapan Cognitive Behavioral Therapy (CBT) dalam setting rehabilitasi khusus perempuan di Yayasan Karunia Insani Rumah Female, Rejang Lebong. Metode yang digunakan adalah kualitatif deskriptif dengan pendekatan studi kasus, melibatkan lima informan (dua konselor dan tiga klien perempuan). Data dikumpulkan melalui wawancara mendalam dan observasi, kemudian dianalisis secara tematik. Hasil penelitian menunjukkan bahwa CBT diterapkan melalui tiga tahapan yang terstruktur namun adaptif, yaitu: (1) tahap awal yang menekankan pembentukan hubungan terapeutik berbasis sensitivitas gender dan perumusan masalah secara kolaboratif; (2) tahap tengah yang berfokus pada restrukturisasi kognitif dengan mengintegrasikan pengalaman hidup klien serta pemicu kekambuhan; dan (3) tahap akhir yang menekankan penguatan perilaku melalui evaluasi reflektif dan penugasan rumah. Kebaruan penelitian ini terletak pada adaptasi kontekstual CBT terhadap kerentanan psikososial perempuan dalam rehabilitasi berbasis komunitas. Temuan menunjukkan bahwa pendekatan ini efektif meningkatkan kesadaran kognitif, regulasi emosi, dan komitmen pemulihan klien.